INDEPENDENT DEVELOPMENT, AND THE A RANGE OF ITS ACHIEVEMENT IN CHOSEN ARABIC COUNTRIES FOR PERIOD (1980 -2010) - Salim Al-Youzbaki; Asmaa Mahmood Fathallah Al-Mansor (Mesopotamia Journal of Agriculture)
The aim of this study is measuring the range of achievement of indevelopment development in the countries of sample by using the mathematical method and measuring the factors which effect on indicators of independent  development by using the econometrica method in analysis , Independent development is considered the alternative distinguished style with balanced strategy with independence in identifying the needs and capabilities. It is a comprehensive, balanced and conscious with its trends, objectives and its relations with other countries. The countries of the sample (Iraq, Syria, Libya and Algeria) adopted this style to overcome their economic and social crises , to improve their conditions , to get rid of underdevelopment, dependency and to build and develop their societies. which become an important and critical issue now and in future. The research has concluded that the countries of the sample have capabilities and qualifications that enable them to achieve this independent development on one hand and that achieving this development varied amongst those countries on the other. We see that Syria is in the independence stage and this stage enables it from accomplishing its goals and providing its requirements to a large degree. For Algeria, it is currently in the transitional stage a way to accomplish independency. While Iraq and Libya now are in the stage of dependency in depending greatly on other countries in order to provide their goods and services. The research also reached several conclusions and recommendations